Cardiorenal syndrome in renal transplant recipients — It's the fistula at fault: A case series. Issue 11 (23rd October 2018) - Samarendra, Padmaraj; Ramkumar, Mohan; Sharma, Vivek; Kumari, Sarita
Abstract: Complications arising from a functional arteriovenous fistula (AVF) in successful kidney transplant recipients (KT) have been overlooked despite some reports of its deleterious effect on heart, lungs, and kidney allograft. As such, there is no consensus regarding management of AVF after renal transplantation. We report Cardio‐Renal Syndrome Type 5 in kidney transplant recipients who presented with a clinical syndrome of shortness of breath, edematous state, kidney allograft dysfunction, and high pulmonary pressure 3‐8 months after successful transplantation. Investigations showed this to be due to high flow functioning AVF (>2 L/min) behaving like a systemic shunt causing high output heart failure, along with pulmonary and venous hypertension. This led to allograft dysfunction of fluid homeostasis. Symptoms resolved with cessation or reduction of AVF flow. Right heart catheterization and echocardiographic features indicating the syndrome are discussed to help clinicians identify the entity and decide management strategy for these AVF.